An Astronomical Diary or Almanack For the Year of Christian Aera 1789. Being the first Year after Bissextile or Leap Year, and the Thirteenth of the Independence of America. - Low, Nathanael, 1792-1883. (Tufts University. Tisch Library., 2018)
12 leaves. Tisch Library copy contains handwritten annotations.